Changing trend in eating away from home and its impact on obesity among Chinese adults aged 18 and over: 2002 - 2015 - Xiao-qi WEI; La-hong JU; Dong-mei YU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the trend of eating away from home (EAFH) and its influence on obesity among Chinese adults from 2002 to 2015. MethodsThe data on 44394, 37703 and 77944 residents aged 18 years and above were extracted from three waves of China National Nutrition and Health Survey (CNNHS) conducted during 2002, 2010 - 2012 and 2015 across the country. The proportion and trend of EAFH among the adults by demographic and social-economic factors were analyzed with Chi-square and Cochran-Armitage trend test. Multivariate logistic regression analysis was used to explore influencing factors of EAFH and the influence of EAFH on obesity. ResultsAmong all the participants surveyed in 2002, 2010 - 2012, and 2015, the proportions of reporting EAFH in past week were 7.2%, 16.5%, and 20.2%, with a significant increasing trend (P < 0.0001); for the male and female participants, the proportions were 9.8%, 20.0%, and 25.1% and 5.0%, 13.8%, and 15.8%, respectively, both with a significant increasing trend (P < 0.0001). The results of multiple logistic regression showed that the participants with following characteristics were more likely to have EAFH: being male, at ages of 18 - 44 years, unmarried, with the annual household income of ≥ 20 000 yuan RMB per capita, having the education of college and above, and being on-the-job workers of other than agriculture, forestry, animal husbandry, fisheries and water conservancy industry; the results also revealed that the male participants reporting EAFH were at an increased risk of obesity (odds ratio [OR] = 1. 166, ( 95% confidence interval [95% CI]: 1.101 - 1.235; P = 0.002), but the females with EAFH were at a decreased risk of obesity (OR = 0.922, 95% CI: 0.861 - 0.986, P = 0.001). ConclusionDuring 2002 - 2015 among Chinese adults aged 18 and above, the proportion of EAFH showed an increasing trend; the proportion was higher and the increasing trend was more obvious among the 18 - 44 years old unmarried adults with higher education and income. Frequent EAFH could increase obesity risk in the population. The results suggest that health education relevant to EAFH should be promoted among adult population in China.